2015
DOI: 10.1038/bmt.2015.170
|View full text |Cite
|
Sign up to set email alerts
|

FLT3 mutational status is an independent risk factor for adverse outcomes after allogeneic transplantation in AML

Abstract: Allogeneic HCT has been increasingly used in the setting of FLT3 mutated AML. However, its role in conferring durable relapse-free intervals remains in question. Herein, we sought to investigate FLT3 mutational status on transplant outcomes. We conducted a retrospective cohort study of 262 consecutive AML patients who underwent first-time allogeneic HCT (2008-2014), of whom 171 had undergone FLT3-ITD mutational testing. FLT3 mutated AML was associated with nearly twice the relapse risk (RR) compared with those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…The presence of FLT3 ‐ITD/ NPM1 ‐WT did not significantly affect CR rates, however, due to increased relapse rates and poor salvage rates, the EFS as well as the OS in patients with FLT3 ‐ITD/ NPM1 ‐WT AML was low as shown in previous studies . Remarkably, previous trials observed an identical high relapse rate of >60% and OS < 40% for FLT3 ‐ITD‐positive patients receiving allo‐HSCT in CR1 and those not receiving a transplant in CR1 . At present, several FLT3 ‐inhibiting tyrosine kinase inhibitors, such as sorafenib and PKC412, are being evaluated in clinical trials .…”
Section: Discussionmentioning
confidence: 43%
“…The presence of FLT3 ‐ITD/ NPM1 ‐WT did not significantly affect CR rates, however, due to increased relapse rates and poor salvage rates, the EFS as well as the OS in patients with FLT3 ‐ITD/ NPM1 ‐WT AML was low as shown in previous studies . Remarkably, previous trials observed an identical high relapse rate of >60% and OS < 40% for FLT3 ‐ITD‐positive patients receiving allo‐HSCT in CR1 and those not receiving a transplant in CR1 . At present, several FLT3 ‐inhibiting tyrosine kinase inhibitors, such as sorafenib and PKC412, are being evaluated in clinical trials .…”
Section: Discussionmentioning
confidence: 43%
“…Genomic instability may result from increased DNA double-strand breaks associated with increased reactive oxygen species generation and from error-prone DNA double-strand break repair [8]. HSCT is the preferred treatment for FLT3-ITD AML patients in remission, but outcomes are inferior to those of patients without FLT3-ITD due to a high rate of early relapses, suggesting the potential utility of treatments targeting FLT3 signaling after transplant [9]. …”
Section: Tyrosine Kinase Receptor Flt3mentioning
confidence: 99%
“…Allogeneic hematopoietic stem cell transplant (alloHSCT) is often recommended for patients with FLT3‐ITD + acute myeloid leukaemia (AML) due to poor prognosis but the presence of FLT3‐ITD also portends a poor post‐transplant outcome . In addition, patients with FLT3‐ITD AML tend to have a poor outcome despite hematopoietic stem cell transplant (HSCT) with higher rates of relapse . As a result, clinicians have studied various medications in an attempt to reduce rates of relapse using various tyrosine kinase inhibitors (TKIs) to block the constitutively activated FLT3 kinase.…”
Section: What Is Known and Objectivementioning
confidence: 99%